Hyperbolic Nanoparticles on Substrate with Separate Optical Scattering and Absorption Resonances: A Dual Function Platform for SERS and Thermoplasmonics. Issue 20 (13th August 2021) - Zhao, Yingqi; Hubarevich, Aliaksandr; Iarossi, Marzia; Borzda, Tetiana; Tantussi, Francesco; Huang, Jian‐An; De Angelis, Francesco
Abstract: Tuning optical properties of plasmonic nanostructures, including their absorption, scattering, and local‐field distribution is of great interest for various applications that rely on optical energy regulated by plasmonic effects. Conventional plasmonic nanostructures enhance light scattering and absorption simultaneously, leading to compromise for either surface‐enhanced spectroscopy or thermoplasmonic applications. In this paper, a dual functional platform based on a hyperbolic meta particles (HMP) substrate that exhibits separate and tuneable wavelengths of absorption and scattering resonances for both thermoplasmonics and surface enhanced Raman spectroscopy (SERS), is demonstrated. Significantly, either light‐to‐heat conversion efficiency at the absorption resonance band or SERS performance at the scattering resonance band of the HMP substrate is improved in comparison to those of plasmonic gold nanoparticles. Taking advantage of the flexible control of the separate scattering and absorption channels, the influence of the absorption resonance band position on the SERS signal is also investigated. The platform shows unique potential for in vitro biosensing in thermal modulation and in situ monitoring. Abstract : A dual functional platform based on a hyperbolic meta particles (HMP) substrate is demonstrated, which exhibits separate wavelengths of absorption and scattering resonances for both thermoplasmonics and surface enhanced Raman spectroscopy (SERS). Either light‐to‐heat conversion efficiency at the absorption resonance band or SERS performance at the scattering resonance band of the substrate is improved in comparison to plasmonic gold nanoparticles.